Influence of mRNA expression of epiregulin and amphiregulin on outcome of patients with metastatic colorectal cancer treated with 5‐FU/LV plus irinotecan or irinotecan plus oxaliplatin as first‐line treatment (FIRE 1‐trial). Issue 3 (18th September 2015) - Stahler, A.; Heinemann, V.; Giessen‐Jung, C.; Crispin, A.; Schalhorn, A.; Stintzing, S.; Fischer von Weikersthal, L.; Vehling‐Kaiser, U.; Stauch, M.; Quietzsch, D.; Held, S.; von Einem, J.C.; et al.
Abstract : Our aim was to investigate the impact of EREG and AREG mRNA expression (by RT‐qPCR) in patients with metastatic colorectal cancer (mCRC). In addition, epidermal growth factor receptor (EGFR) expression (by immunohistochemistry) as well as RAS‐ and PIK3CA‐ mutations (by pyrosequencing) were assessed. Tumors of 208 mCRC patients receiving 5‐fluorouracil/leucovorin plus irinotecan (FUFIRI) or irinotecan plus oxaliplatin (mIROX) within the FIRE‐1 trial were analyzed for mutations. Molecular characteristics were correlated with response, progression‐free survival (PFS), overall survival (OS). mRNA expression was evaluated using ROC‐analysis in 192 tumors (AREG high n  = 31 vs . low n  = 161; EREG high n  = 89 vs . low n  = 103). High versus low AREG expression was associated with PFS of 10.0 versus 8.0 months (HR = 0.62, 95% CI: 0.402–0.940, p  = 0.03) and OS of 24.6 versus 18.7 months (HR = 0.72, 95% CI: 0.476–1.078, p  = 0.11). High versus low EREG expression correlated with prolonged PFS (9.4 vs . 6.8 months, HR = 0.62, 95% CI: 0.460–0.846, p  = 0.002) and OS (25.8 vs . 15.5 months, HR = 0.48, 95% CI: 0.351–0.657, p  < 0.001). The positive prognostic effect of high EREG expression was confirmed in a multivariate analysis and was neither affected by EGFR expression nor by mutations of RAS ‐ and PIK3CA ‐genes. EREG expression appears as an independent prognostic marker in patients with mCRC receiving first‐line irinotecan‐based chemotherapy. Abstract : What's new? Expression levels of an EGFR ligand could help predict survival for metastatic colorectal cancer, according to new analysis. It has been reported that high EGFR ligand expression might be associated with favourable outcome of patients treated EGFR‐targeted antibodies. To further investigate the prognostic impact of ligand expression, the authors tested the mRNA levels of two EGFR ligands, epiregulin and amphiregulin in a cohort of patients treated with chemotherapy alone, and correlated expression with patient survival. High epiregulin expression, they found, indicated better outcome.